PENGEMBANGAN MEDIA APLIKASI ANDRIOD MA’CAKU BERBASIS BUDAYA LOKAL - Hasriani (Jurnal Pendidikan Dasar, 2022)
The purpose of this research is to develop learning media for android applications based on local culture. This research stage uses the Four-D model stage which consists of define, design, development, and disseminate stages. The data analysis technique used is descriptive qualitative analysis and descriptive quantitative. The results showed that the activities of students during learning using Ma'caku media during field trials obtained an achievement rate of 89.00% with a very active category so that the product could be used without revision. Based on all the results of product analysis including validity, practicality, attractiveness, and effectiveness, it can be concluded that the development of android applications based on local culture with material presented in Ma'caku media in the form of apk files, the main software in this development product is Smart App Creator 3 while the software Support is powerpoint, paint, corel draw. Powerpoint, corel draw and paint are used to combine and edit image assets, while SAC3 software is used to work on and create applications Keywords:Ma'caku Application, Poetry, Local Culture